2018
DOI: 10.1039/c7nj04271j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel 1,2,3-triazole based artemisinin derivatives and their antiproliferative activity

Abstract: Novel artemisinin-1,2,3-triazole derivatives show significant antiproliferative activity, and induce apoptosis and ROS generation and arrest the cell cycle at the G2/M phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Similarly, a novel series of artemisinlcone hybrids ( 24 , 25 ) prepared by Gaur et al showed potent activity against HL-60 (leukemia), Mia PaCa-2 (pancreatic cancer), PC-3 (prostate cancer), LS180 (colon cancer) and HEPG2 (hepatocellular carcinoma) cancer cell lines with a high selectivity index [ 69 ]. Kapkoti et al designed 1,2,3-triazole-containing artemisinin–chalcone hybrids ( 26 , IC 50 : 7.16–57.18 µM; 27 , IC 50 : 17.14–69.67 µM) displaying remarkable activity against K562 (human chronic myeloid leukemia cell), PC-3 (human prostate cancer cell), A431 (human skin squamous cell carcinoma), MDA-MB-231 (human metastatic breast cancer cell line), COLO-205 (human colon cancer cell), A549 (human lung cancer cell), and HEK-293 (human embryonic kidney cell) cancer cell lines with significant induction of ROS formation [ 70 ]. Moreover, a toxicity study on human erythrocytes revealed that these molecules are nontoxic (IC 50 : >100 μg/mL).…”
Section: Strategies Employed To Produce Anticancer Chalconesmentioning
confidence: 99%
“…Similarly, a novel series of artemisinlcone hybrids ( 24 , 25 ) prepared by Gaur et al showed potent activity against HL-60 (leukemia), Mia PaCa-2 (pancreatic cancer), PC-3 (prostate cancer), LS180 (colon cancer) and HEPG2 (hepatocellular carcinoma) cancer cell lines with a high selectivity index [ 69 ]. Kapkoti et al designed 1,2,3-triazole-containing artemisinin–chalcone hybrids ( 26 , IC 50 : 7.16–57.18 µM; 27 , IC 50 : 17.14–69.67 µM) displaying remarkable activity against K562 (human chronic myeloid leukemia cell), PC-3 (human prostate cancer cell), A431 (human skin squamous cell carcinoma), MDA-MB-231 (human metastatic breast cancer cell line), COLO-205 (human colon cancer cell), A549 (human lung cancer cell), and HEK-293 (human embryonic kidney cell) cancer cell lines with significant induction of ROS formation [ 70 ]. Moreover, a toxicity study on human erythrocytes revealed that these molecules are nontoxic (IC 50 : >100 μg/mL).…”
Section: Strategies Employed To Produce Anticancer Chalconesmentioning
confidence: 99%
“…1,2,3-Triazole-tethered dihydroartemisinin-chalcone hybrid 63 (Figure 11, IC 50 : 7.16 μm, MTT assay) display comparable activity to doxorubicin (IC 50 : 6.36 μm), but it is more potent than dihydroartemisinin (IC 50 : 43.43 μm) against A549 cells, and this hybrid (IC 50 : > 100 μm) is nontoxic toward human erythrocyte and normal kidney cells (HEK-293) (Kapkoti et al, 2018). An SAR study implies that incorporation of the second dihydroartemisinin moiety could boost the activity to some extent.…”
Section: Miscellaneous 123-triazole-containing Compoundsmentioning
confidence: 99%
“…Notably, triazole rings exhibit various medicinal applications, such as usages as anticancer [18] anti-HIV [19], antimalarial [20], antiplasmodial [21], and antibacterial agents [1,22]. Some significant triazole derivatives in this context are shown in Figure 1 [8,[23][24][25][26][27]. As such, there is still a demand for the expansion of ways to access new 1,2,3-triazole heterocyclic rings in rapid, efficient, and versatile ways.…”
Section: Introductionmentioning
confidence: 99%